The Relationship between Urothelial Type Bladder Cancer, Plasma 25-Hydroxyvitamin D Levels, and Vitamin D Receptor ApaI BsmI FokI, and TaqI Polymorphisms - (:unkn) unknown (CLIN LAB PUBL, 2019)
Background: Bladder cancer is an important health problem which ranks 4th among most frequently seen cancer types in men. In our study we aimed to investigate the correlations among urothelial type bladder cancer polymorphisms, ApaI, BsmI, Fold, and Taal, prevalently observed in the vitamin D receptor (VDR) gene and plasma vitamin D levels in a Turkish population. Methods: Our study included 101 patients and 109 control subjects. Plasma 25(OH)D levels were determined using a HPLC method and VDR gene polymorphisms with PCR-RFLP method. Results: A statistically significant intergroup difference was not observed with regard to age, gender, and BMIs of the patients. Median (min - max) 25(OH)D levels in the patient and the control groups were determined as 11.9 ng/dL (1.9 - 33.0 ng/dL) and 9.7 ng/dL (2.1 - 39.5 ng/dL), respectively. A statistically significant intergroup difference was not observed with regard to 25(OH)D levels (p = 0.402). A statistically significant intergroup difference was not observed with regard to genotype distribution of ApaI, Bsml, and Taal polymorphisms and allele frequencies. Control and urothelial type bladder cancer groups showed a statistically significant difference with respect to genotype distribution of Fold polymorphism (p = 0.048). However in a binary logistic regression model, when corrected OR values were estimated by including smoking history in the model, the correlation detected between the presence of FF and increased risk of disease was not statistically significant (ORadj = 1.64, 95% CI = 0.89 - 3.02, p = 0.114). Conclusions: In the light of the data concerning Turkish population a statistically significant correlation could not be demonstrated between plasma vitamin D levels, ApaI, BsmI, FokI, and TaqI polymorphisms, and urothelial type bladder cancers. Since literature data are limited in number, further studies should be conducted in larger patient groups.
Keywords: vitamin D; bladder cancer; polymorphism; TRANSITIONAL-CELL CARCINOMA; GENE POLYMORPHISMS; RISK; ASSOCIATION